Fisionomia das savanas de Roraima, Brasil - Miranda, Izildinha Souza; Absy, Maria Lúcia (Acta Amazonica, 2000)
Forty five plots of 0,15ha (10 X 150m) distributed in the savannas of Roraima were analysed for physiognomy and their relationship to the edaphic characteristics of the surface soil. Quantitative measures of height, frequency, basal area and density of woody elements and qualitative measures of spatial distribution and % cover of tree/shrubs were used. The plots were classified in to four physiognomic types (grassland, tree and shrub savanna, woodland savanna and park savanna) each with very defined structural characteristics. The survey found 267 species , belonging to 55 families, 137 genera, 195 herbaceous species and 71 woody species. Among the woody, 51% were tree , 32% shrub and 17% dwarf shrubs. The herbaceous stratum is the richest, with 41 families, 98 genera and 207 species. However, only 18 species were found in more than 20% of the plots. Eighty percent of the plots classified as grassland were found on sandy soils, 81% of the tree and shrub savanna on clay soils, 64% of the woodland savanna on sandy soils and all the parks savannas were found on soils of loamy sand. However, the physiognomic types did not possess significant relationships with most of the analyzed nutrients; only the levels of A1+++, in the surface layer (0-10cm depth), were significantly different among the physiognomic types. That significant difference was due mainly to the differences found between the levels of A1+++ of the grassland and tree and shrub savanna and between the grassland and woodland savannas.
Physiognomy of the savannas of Roraima, Brazil
Keywords: Physiognomy; Savannas; Roraima; Fisionomias; Savanas; Roraima